Jarcho-Levin Syndrome A Case Report - Naher, Begum Sharifun; Sarkar, Adity (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Jarcho- Levin Syndrome is an eponym that represents a spectrum of short trunk skeletal dysplasia with variable involvement of the vertebrae and ribs. Initialy considered to be lethal, it is now accepted as compatible with life in its milder presentations. Neural tube defect is a rare association in Jarcho-Levin Syndrome. Here we report a case of Jarcho- Levin Syndrome with meningomyelocele in a newborn. J Bangladesh Coll Phys Surg 2015; 33(4): 222-224